Isolation of novel cold-tolerance genes from rhizosphere microorganisms of Antarctic plants by functional metagenomics - de Francisco Martínez, Patricia; Morgante, Verónica; González-Pastor, José Eduardo (Frontiers in Microbiology, 2022)
The microorganisms that thrive in Antarctica, one of the coldest environments on the planet, have developed diverse adaptation mechanisms to survive in these extreme conditions. Through functional metagenomics, in this work, 29 new genes related to cold tolerance have been isolated and characterized from metagenomic libraries of microorganisms from the rhizosphere of two Antarctic plants. Both libraries were hosted in two cold-sensitive strains of E. coli: DH10B ΔcsdA and DH10B ΔcsdA ∆rnr. The csdA gene encodes a DEAD-box RNA helicase and rnr gene encodes an exoribonuclease, both essential for cold-adaptation. Cold tolerance tests have been carried out in solid and liquid media at 15°C. Among the cold tolerance genes identified, 12 encode hypothetical and unknown proteins, and 17 encode a wide variety of different proteins previously related to other well-characterized ones involved in metabolism reactions, transport and membrane processes, or genetic information processes. Most of them have been connected to cold tolerance mechanisms. Interestingly, 13 genes had no homologs in E. coli, thus potentially providing entirely new adaptation strategies for this bacterium. Moreover, 10 genes also conferred resistance to UV-B radiation, another extreme condition in Antarctica.